Old babes in the wood : stories - Atwood, Margaret (New York : Doubleday, 2023)
"Margaret Atwood has established herself as a beloved cultural icon and one of the most visionary and canonical authors of her generation. In this collection comprised of fifteen extraordinary stories-some of which have appeared in The New Yorker and The New York Times Magazine-Atwood speaks to our times with her characteristic wit and intellect. Of special significance are the seven works revolving around the long-term married couple Tig and Nell. Acting as bookends for the collection, these stories look deeply in the heart of what it means to spend a life together, with the four stories in Part I relating tales from their married life, and the three stories at the end showing Nell's reality in the aftermath of Tig's death. In other works, two sisters grapple with loss and memory in "Old Babes in the Wood"; "Impatient Griselda" reprises the folkloric role of Griselda in Bocaccio's The Decameron, exploring alienation and miscommunication; and "Evil Mother" touching on the fantastical, examining a mother-daughter relationship in which the mother purports to be a witch. Returning to short fiction for the first time since her 2014 collection, Stone Mattress, Atwood's storytelling gifts and unmistakable style are on full display"--
Keywords: Short stories